Mutations in the Phenicol Exporter Gene fexA Impact Resistance Levels in Three Bacterial Hosts According to Susceptibility Testing and Protein Modeling - Müller, Anja; Sakurai, Keisuke; Seinige, Diana; Nishino, Kunihiko; Kehrenberg, Corinna (Frontiers in Microbiology, 2022)
The prototype fexA gene confers combined resistance to chloramphenicol and florfenicol. However, fexA variants mediating resistance only to chloramphenicol have been identified, such as in the case of a Staphylococcus aureus isolate recovered from poultry meat illegally imported to Germany. The effects of the individual mutations detected in the fexA sequence of this isolate were investigated in this study. A total of 11 fexA variants, including prototype fexA and variants containing the different previously described mutations either alone or in different combinations, were generated by on-chip gene synthesis and site-directed mutagenesis. The constructs were inserted into a shuttle vector and transformed into three recipient strains (Escherichia coli, Staphylococcus aureus, Salmonella Typhimurium). Subsequently, minimal inhibitory concentrations (MIC) of florfenicol and chloramphenicol were determined. In addition, protein modelling was used to predict the structural effects of the mutations. The lack of florfenicol-resistance mediating properties of the fexA variants could be attributed to the presence of a C110T and/or G98C mutation. Transformants carrying fexA variants containing either of these mutations, or both, showed a reduction of florfenicol MICs compared to those tranformants carrying prototype fexA or any of the other variants. The significance of these mutations was supported by the generated protein models, indicating a substitution towards more voluminous amino-acids in the substrate-binding site of FexA. The remaining mutations, A391G and C961A, did not result in lower florfenicol-resistance compared to prototype fexA.